Effects of pH, temperature and solids loading on microbial community structure during batch culture on a polymetallic ore - Watling, Helen; Collinson, David; Shiers, Denis; Bryan, Christopher; Watkin, Elizabeth (Elsevier, 2013)
The bioleaching of an organic-rich polymetallic ore was conducted under conditions intended to probe the boundaries of microbial activity using iron and sulphur oxidising microorganisms and heterotrophs enriched from self-heating pyritic coal. Solution chemistry parameters such as rapidly increased ORP and reduction in pH subsequent to inoculation point to the development of active microbial communities. The ease with which communities adapted to the organic-rich ore and the bioleaching systems indicated that the organic compounds were not present in leachates at toxic levels. Overall, extractions obtained in three series of inoculated tests were at 35 °C: 79–96% Zn, 48–82% Cu, 47–55% Ni and 79–86% Co; at 55 °C: 96–97% Zn, 72–80% Cu, 46–50% Ni and 82–83% Co. T-RFLP provided semi-quantitative estimates of species abundance. The greatest microbial complexity was observed with moderate pH and low solids loading. Microbial complexity was reduced significantly by low pH or increased solids loading. Nevertheless, efficient bioleaching was observed over a relatively wide range of operating conditions. Even under the more extreme conditions, the community profile was dominated by combinations of organisms not typically seen in most commercial operations.